Peningkatan Pendidikan Keluarga Melalui Pengembangan Parenting Berbasis Islami - Indrawati, Triana; Pramana, Wirayudha; Hermawan, Ambar (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2020)
This research is motivated by the level of violence that is often done by parents against children who are involved in inappropriate families, this is caused by the knowledge and understanding of parents in the process of educating and caring for children in the family. The purpose of this research is to analyze and describe the improvement of family education through the development of Islamic-based parenting. Parenting results can build good communication between institutions and parents. Related to the pattern of care carried out at the institution and applied by parents at home in harmony, through parenting activities also parents can find out the achievements of the child's development, what basic rights must be completed by parents in the development of children, and provide assistance to parents . Then, continue to be friendly to children, take part in parenting child-friendly activities in educating, guiding and caring within the family, increasing in various aspects. This must be instilled the values ​​of Islamic religious education in the framework of forming the character of good teenagers. In essence, parents are role models for children as real teachers for children. If parents show a good example, then the child will also have a good temperament and vice versa.